2016
DOI: 10.1007/s00125-016-3879-6
|View full text |Cite
|
Sign up to set email alerts
|

Sources of beta cells inside the pancreas

Abstract: The generation of beta(-like) cells to compensate for their absolute or relative shortage in type 1 and type 2 diabetes is an obvious therapeutic strategy. Patients first received grafts of donor islet cells over 25 years ago, but this procedure has not become routine in clinical practice because of a donor cell shortage and (auto)immune problems. Transplantation of differentiated embryonic and induced pluripotent stem cells may overcome some but not all the current limitations. Reprogramming exocrine cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In humans is about 50-60% while in rodents reaches 80%, 4 therefore, alterations of b-cells directly affect the islet area. Mechanisms such as b-cell neogenesis (differentiation from precursor cells), b-cell proliferation and transdiferentiation, and b-cell hypertrophy are responsible for b-cell mass increase; 5,6,7,8,9 while, b-cell reduction is determined by apoptosis and b-cell atrophy. 5,7 Studies in obese or diabetic rodent models have shown that exercise counter-regulates the IRS2-PI3K-pAkt growth pathway attenuated in Langerhans islet resulting in a bigger b cell area, major b cell proliferation rate and lower apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In humans is about 50-60% while in rodents reaches 80%, 4 therefore, alterations of b-cells directly affect the islet area. Mechanisms such as b-cell neogenesis (differentiation from precursor cells), b-cell proliferation and transdiferentiation, and b-cell hypertrophy are responsible for b-cell mass increase; 5,6,7,8,9 while, b-cell reduction is determined by apoptosis and b-cell atrophy. 5,7 Studies in obese or diabetic rodent models have shown that exercise counter-regulates the IRS2-PI3K-pAkt growth pathway attenuated in Langerhans islet resulting in a bigger b cell area, major b cell proliferation rate and lower apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Harry Heimberg [6] considered the sources of beta cells available within the pancreas, with emphasis on the benefits of reprogramming the abundant populations of exocrine cells into fully functional beta cells. He summarised data from his group using the partial duct ligation (PDL) and growth factor therapy models to define the conditions necessary for exocrine to beta cell reprogramming.…”
mentioning
confidence: 99%